CT SNAP 2011 : reconsidering a failing process for granting food aid - Kinkead, Gwen, 1951-; Elias, Jaan; Chahine, Teresa; Meng, Lesley; Alizamir, Saed (London : Yale School of Management, 2021)
In this case, Roderick Bremby is tasked with developing a plan to address challenges faced by the Connecticut Supplemental Nutrition Program (SNAP). Without immediate change, CT SNAP could fail to provide thousands of people with necessary food aid. Therefore, Bremby must devise strategies for CT SNAP that maximize operational support and preserve assistance for users.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Food relief -- Connecticut -- Case studies